Globalization and urban centers: Impact, challenges and development of global cities - Mujević Demir (Zbornik radova Departmana za geografiju, turizam i hotelijerstvo)
The paper focuses on globalization and its impact on the world's urban centers, i.e., on the interaction of globalization and (large) cities. The globalization of cities refers to the process by which the cities become increasingly involved in global economic, political, social and cultural networks. This process means that cities, especially large and important urban centers, become key actors on the international scene, transcending national borders and establishing a direct connection with global markets, cultures, communications and political structures. Special attention is devoted to the development of the so-called global cities, which represent key centers of economic, political and cultural power. The environmental challenges that globalized cities bring are also examined. Finally, the paper considers specific aspects of globalization within the context of Montenegro, analyzing how global processes affect development in that country.